PENGARUH PENGAWASAN, KARAKTERISTIK PEKERJAAN DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI KANTOR CAMAT PANDAN KABUPATEN TAPANULI TENGAH - Ainun Panggabean; Siti Aisyah Harahap; Suhendrik Suhendrik; Suherman Siregar; Sulton Aman Hasibuan (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
The formulation of problem in this research is there is influence leadership on employees performance. There is influence job characteristic on employees performance. There is controlling on employees performance. There is influence of leadership, job characteristic and controlling on employees performance. The purpose of this research is for know influence and analize of leadership on employees performance. For know influence and analize job characteristic on employees performance. For know influence and analize controlling on employees performance. For know influence and analize leadership, job characteristic and controlling on employees performance. The sample in this research is 31 employees, with data analysis technique used is multiple linear regression analysis. The research result leadership influence positive and significant on employees performance. Job characteristic influence positive and significant to employees performance. Controlling influence positive and significant to employees performance. Leadership, job characteristic and controlling influence positive and significant to employees performance.